Acidentes de trânsito em capitais selecionadas do Brasil: estimativa da magnitude corrigida e fatores associados à gravidade da lesão - Mandacarú, Polyana Maria Pimenta (2017)
Introduction: Middle-and low-income countries currently account for 92% of all road transport fatalities worldwide, with an increasing trend in mortality rates, the opposite of what occurs in high-income countries. Brazil has a high morbidity and mortality burden caused by traffic. However, one of the limitations of the knowledge of the real magnitude of traffic accidents in Brazil is the lack of qualified information about traffic accidents by mode of transportation and the underestimation of the actual number of fatalities and serious injuries. In this way, the qualification of the databases through the relationship of health and traffic records allows improving coverage, coverage and quality of information, as well as enhances the epidemiological analysis of this disease in the population. Objectives: To estimate the magnitude of deaths and severe injuries using a linkage procedure as well as the percentage of correction for health and traffic data sources in the municipalities of Belo Horizonte, Campo Grande, Curitiba, Palmas, Teresina and Goiania, and to characterize the factors Associated with deaths and serious injuries in Goiania. Method: Two cross-sectional studies were conducted, using a database of traffic victims (VIT), the Hospital Inpatient System (SIH), and the Mortality Information System (SIM). The first in Belo Horizonte, Campo Grande, Curitiba, Palmas and Teresina and the second in Goiania. A linkage procedure was performed in both studies through the RECLINK III program, identifying true pairs with calculation of the percentage of correction of the underlying cause of death, secondary diagnosis or classification of the victim in the traffic database. In the second study, for the definition of the associated factors for deaths and severe injuries, the incidence ratios with a 95% confidence interval were estimated. The comparison of the incidences between the categories of each variable using bivariate and multivariable regression model using the Poisson regression, with robust variance. Results: The results showed that there was a considerable correction of the basic cause of death, diagnosis of hospitalization or classification of the severity of the victim's injury in traffic records in the six capitals. For SIM, the percentage of correction of the underlying cause of death was 29.9%, 11.9%, 4.2%, 33.5%, and 43.9% for Belo Horizonte, Campo Grande, Curitiba, Teresina and Goiania, respectively. For SIH, the percentage of correction of the secondary diagnosis of hospitalization was 51.3% for Goiania, 24.4% for Belo Horizonte, 96.9% for Campo Grande, 100.0% for Palmas and 33.2% for Teresina. For VIT, there was a change in the classification of the severity of the victim (not severe to severe), with correction percentage of 100.0% for Belo Horizonte and Teresina, 48.0% for Campo Grande, 52.8% for Goiania and 51.4% For Palmas. In the case of nonfatal to fatal, the correction was 29.5%, 52.3%, 74.3%, 4.4% and 72.9%, respectively, for Belo Horizonte, Campo Grande, Curitiba, Palmas and Teresina. For Goiania, the contribution of the linkage procedure to the database of victims was the identification of 15 deaths (9.6%), not classified as such in the transit data base. In Goiania, 70% of all victims were males and 43.7% of all victims were aged between 18 and 29 years and 63% of all accidents were motorcycle occupants. The main factors associated with death were: age over 40 years (40-49 years: RI 2.75, IC 1.11-6.79, 50-59 years: RI 4.46, IC 1.8- 11.04 and 60 and more: RI 7.69, IC 3.15-18-78) bicycle occupants (RI 2.26 IC 1.19-4.3) and pedestrians (RI 2.12 IC 1.26 -3.58) and the occurrence of the accident between 0-6 hours (RI 2.47 IC 1.36-4.47); For the severely injured were: the age group over 40 years (40-49 years: RI 1.62, IC 1.26-2.08, 50-59 years: RI 1.48, IC 1.23-2, 16 and 60 and more: RI 2.00, IC 1.50-2.66), occupants of Motorcycle (RI 2.38 IC 2.01-2.83), Bicycle (RI 2.35 IC 1.76- And the occurrence of the accident between the periods of 00: 00-17: 59 hours (00:00 to 05:59 RI 1, 38 IC 1.1-1.73.06.06 at 11.59 RI 0.72 IC 0.63-0.83; 12:00 at 17.59 RI 0.84 IC 0.73-0.95). Conclusion: The study contributed to the qualification of the coverage and quality of the information of the health and traffic data banks, as well as identified gaps and limitations in the information system that registers ATT.